2021
DOI: 10.1182/blood.2020010163
|View full text |Cite
|
Sign up to set email alerts
|

CHIP and hips: clonal hematopoiesis is common in patients undergoing hip arthroplasty and is associated with autoimmune disease

Abstract: Clonal hematopoiesis (CH) is an age-related condition predisposing to blood cancer and cardiovascular disease (CVD). Murine models demonstrate CH-mediated altered immune function and proinflammation. Low-grade inflammation has been implicated in the pathogenesis of osteoarthritis (OA), the main indication for total hip arthroplasty (THA). THA-derived hip bones serve as a major source of 'healthy' hematopoietic cells in experimental hematology. We prospectively investigated frequency and clinical associations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 24 publications
6
35
0
2
Order By: Relevance
“…Although ChIP itself is not considered a malignant stage, at least for now, population-based studies using wholeexome sequencing technology, have revealed~10-fold increased relative risk of developing myeloid malignancies over several years of follow-up in ChIP cases [15][16][17]. Furthermore, researchers have also observed a previously unreported association of ChIP with autoimmune diseases, such as in osteoarthritis patients [18]. Existence of clonal populations in the bone marrow, typically identified by the expansion of more than one genetically distinct cell populations, is increasingly being viewed as a phenomenon named 'inflammaging', the age-associated surge in systemic inflammation (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Although ChIP itself is not considered a malignant stage, at least for now, population-based studies using wholeexome sequencing technology, have revealed~10-fold increased relative risk of developing myeloid malignancies over several years of follow-up in ChIP cases [15][16][17]. Furthermore, researchers have also observed a previously unreported association of ChIP with autoimmune diseases, such as in osteoarthritis patients [18]. Existence of clonal populations in the bone marrow, typically identified by the expansion of more than one genetically distinct cell populations, is increasingly being viewed as a phenomenon named 'inflammaging', the age-associated surge in systemic inflammation (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the healthy samples aged over 60 years, the presence of clonal hematopoiesis was excluded by targeted sequencing of 68 genes recurrently mutated in hematologic malignancies. 16 Furthermore, BM samples were obtained from patients with different BM failure states, such as SDS, an inherited BM failure syndrome, hypocellular MDS, or severe aplastic anemia. We also included 3 samples from leukemia/lymphoma patients undergoing allogeneic HSCT, 2 of which had received total body irradiation as part of their conditioning regimen, which may contribute to niche damage, and the third patient showed incomplete BM reconstitution after transplant (likely due to extensive pretreatment) (supplemental Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that mutational burden increases with age, as described in the so called clonal hematopoiesis of indeterminate potential (CHIP) or clonal cytopenia of undetermined significante (CCUS). Recently, DNMT3A, TET2 and ASXL1 mutations were found in 29.5%, 15.0% and 3.5% of studied patients, with a striking association with autoimmune diseases (38). Regarding BMF, a variable combination of somatic mutations has been largely described: in MDS the most frequently observed involve the splicing genes SF3B1, SRSF2, U2AF1, ZRSR2, the DNA methylation genes DNMT3A, TET2, IDH1, IDH2, and the chromatin modification genes ASXL1, EZH2, KDM6A (39).…”
Section: Autoimmunity In Bmf Syndromes: Mds Hypoplastic Mds and Aamentioning
confidence: 96%